2020
DOI: 10.2807/1560-7917.es.2020.25.39.1900627
|View full text |Cite
|
Sign up to set email alerts
|

Capturing respiratory syncytial virus season in Belgium using the influenza severe acute respiratory infection surveillance network, season 2018/19

Abstract: Background Respiratory syncytial virus (RSV) is a common cause of severe respiratory illness in young children (< 5 years old) and older adults (≥ 65 years old) leading the World Health Organization (WHO) to recommend the implementation of a dedicated surveillance in countries. Aim We tested the capacity of the severe acute respiratory infection (SARI) hospital network to contribute to RSV surveillance in Belgium. Methods During the 2018/19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
0
25
1
Order By: Relevance
“…From 2767 records identified in the systematic literature search, we included 14 articles in the meta‐analysis, 1 , 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 supplemented with data from seven studies identified via citation search (Fowlkes et al 32 ), extraction from the Shi et al meta‐analysis 12 (unpublished studies SP‐RSV11 and SP‐FIM12 and Falsey 2008–2011 data), gray literature (Novavax E201 33 and E301 studies 34 , 35 ), and the RSVVW'21 abstract booklet (Devadiga et al data 4 ). Of the 21 identified studies, 14 reported data on attack rates, eight on hospitalization rates, and eight on hCFR of RSV‐ARI (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2767 records identified in the systematic literature search, we included 14 articles in the meta‐analysis, 1 , 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 supplemented with data from seven studies identified via citation search (Fowlkes et al 32 ), extraction from the Shi et al meta‐analysis 12 (unpublished studies SP‐RSV11 and SP‐FIM12 and Falsey 2008–2011 data), gray literature (Novavax E201 33 and E301 studies 34 , 35 ), and the RSVVW'21 abstract booklet (Devadiga et al data 4 ). Of the 21 identified studies, 14 reported data on attack rates, eight on hospitalization rates, and eight on hCFR of RSV‐ARI (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on eight studies, of which seven were identified from the systematic literature search 1 , 20 , 22 , 23 , 24 , 28 , 31 and one (Falsey 2008–2011) described in Shi et al , 12 the hCFR in adults ≥60‐year‐olds was estimated to be 7.13% (95% CI: 5.40–9.36; range: 2.33–13.64) (Figure 4 ). The number of in‐hospital deaths that occurred in the study from Branche et al 23 across the three RSV seasons in patients from Rochester and New York City hospitals were obtained from unpublished data provided by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Both ILI and SARI surveillances were able to capture the seasonal circulation of influenza virus, but such bell-shape epidemic curves were not detected for other NIRV, with perhaps two exceptions: coronaviruses in the ILI surveillance during season 2016/17 despite the limited number of positive samples ( Supplementary Figure S1 ) and RSV in the SARI surveillance, with the detection of the end of the RSV epidemic, which usually occurs before the influenza epidemic in western Europe [ 13 ] including in Belgium [ 14 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the children are discharged with ongoing signs/symptoms that may drive additional medical resources utilization after hospital discharge. In this study, the MRUs were not captured after discharge, even though we consider that 7 days is sufficient time for capturing the utilization of medical resources [ 22 , 48 ]. Since, only the current breastfeeding status was collected, the study was not able to evaluate the potential impact of prior breastfeeding on clinical burden and medical resources utilization during the hospitalization, In addition, the way different sites recruited participants could be different (some sites could have included mainly sicker patients that have a higher probability of receiving supplemental oxygen).…”
Section: Discussionmentioning
confidence: 99%